Interpretation of the effects of rumen acidosis on the gut microbiota and serum metabolites in calves based on 16S rDNA sequencing and non-target metabolomics - Wu, Fanlin; Ji, Peng; Yang, Haochi; Zhu, Xiaopeng; Wu, Xiaohu (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Rumen acidosis is one of the most common diseases in beef cattle. It severely affects the normal development of calves and poses a significant threat to the farming industry. However, the influence of rumen acidosis on the gut microbiota and serum metabolites of calves is currently unclear. Objective The aim of this study is to investigate the changes in the gut microbiota and serum metabolites in calves after rumen acidosis and analyse the correlation. Methods Eight calves were selected as the rumen acidosis group, and eight health calves were selected as the healthy group. The faecal gut microbiota and serum metabolites of calves were detected respectively using 16S rDNA high-throughput sequencing and non-target metabolomics. The correlation between gut microbiota and serum metabolites was analyzed by Spearman correlation analysis. Results Differential analysis of the diversity and composition of gut microbiota between eight male healthy (Health) and eight male rumen acidosis (Disease) calves revealed that rumen acidosis increased the abundance of the gut microbiota in calves. At the phylum level, compared to the Healthy group, the relative abundance of Proteobacteria in the Disease group significantly decreased (P<0.05), while the relative abundance of Desulfobacterota significantly increased in the Disease group (P<0.05). At the genus level, compared to the Disease group, the relative abundance of Alloprevotella, Muribaculaceae, Succinivibrio, Prevotella, Agathobacter and Parabacteroides significantly increased in the Healthy group (P<0.05), while the relative abundance of Christensenellaceae_R-7 and Monoglobus significantly decreased in the Healthy group (P<0.05). Differential analysis results showed the Healthy group had 23 genera with higher abundance, while the Disease group had 47 genera with higher abundance. Serum metabolomics results revealed the differential metabolites associated with rumen acidosis, including nicotinamide, niacin, L-glutamic acid and carnosine, were mainly enriched in the nicotinate and nicotinamide pathway and the histidine pathway. Conclusion The occurrence of rumen acidosis can induce changes in the gut microbiota of calves, with a significant increase of the Christensenellaceae_R-7 genus and a significant decrease of Prevotella and Succinivibrio genera. In addition, the occurrence of rumen acidosis can also induce changes in serum metabolites including niacin, niacinamide, L-glutamine, and carnosine, which may serve as the diagnostic biomarkers of rumen acidosis of calves.